Three Dimensional-Arterial Spin Labeling Evaluation of Improved Cerebral Perfusion After Limb Remote Ischemic Preconditioning in a Rat Model of Focal Ischemic Stroke - Zheng, Tianxiu; Lai, Xiaolan; Lu, Jiaojiao; Chen, Qiuyan; Wei, Dingtai (Frontiers in Neuroanatomy, 2022)
Purpose To investigate the application value of 3D arterial spin labeling (3D-ASL) for evaluating distal limb ischemic preconditioning to improve acute ischemic stroke (AIS) perfusion. Materials and Methods A total of 40 patients with AISs treated in our hospital from January 2020 to December 2020 were recruited, and 15 healthy individuals who were examined in our hospital during the same period were included as the control group; all of these participants were scored on the National Institutes of Health Stroke Scale (NIHSS) and examined by MRI. Sequences included conventional sequences, diffusion-weighted imaging (DWI), magnetic resonance angiography (MRA), and 3D-ASL, and cerebral infarct volume and cerebral blood flow (CBF) in the area of the infarct lesion were measured. After 3 months of treatment, patients with AIS were scored on the modified Rankin Scale (mRS) and divided into good prognosis and poor prognosis groups. In total, 55 adult male Sprague–Dawley rats were divided randomly into three groups: 20 in the middle cerebral artery occlusion (MCAO) group, 20 in the MCAO + limb remote ischemic preconditioning (LRP) group, and 15 in the sham group. In total, 48 h after the procedures, conventional MRI, DWI, and 3D-ASL sequence data were collected, and 2,3,5-trphenyltetrazolium chloride monohydrate (TTC) staining and behavioral scoring were performed. CBF was recorded in the infarct lesion area and the corresponding contralateral area, and the affected/contralateral relative values (rCBF) were calculated to compare the differences in rCBF between different groups. The pathological changes in brain tissues were observed by HE staining, and the expression of vascular endothelial growth factor (VEGF) and platelet endothelial cell adhesion molecule-1 (PECAM-1/CD31) in brain tissues was detected by immunofluorescence and real-time quantitative polymerase chain reaction (RT-qPCR). The protein expression of VEGF was detected by western blotting. Results Hypertension and internal carotid atherosclerosis are high-risk factors for ischemic stroke, and CBF values in the infarct area are significantly lower than those in the corresponding areas on the contralateral side. NIHSS and mRS scores and CBF values have higher specificity and sensitivity for the prognosis of patients with AIS. LRP significantly reduces the infarct area, improves behavioral deficits in rats with cerebral ischemia, reduces neurological injury and histological damage, protects vascular structures, and promotes neovascularization. In addition, 3D-ASL showed a significant increase in brain tissue perfusion in the ischemic area after LRP, and the expression of VEGF and CD31 showed a significant positive correlation with CBF values. Conclusion Three dimensional (3D) ASL can be used to evaluate LRP to improve stroke perfusion, and its protective effect may be closely related to LRP-induced vascular regeneration.